PENGEMBANGAN BEBE ANAK DENGAN SUMBER IDE HEWAN KELINCI UNTUK ANAK USIA 5 TAHUN - safaamalia; Sugiyem, Sugiyem (Universitas Negeri Jakarta, 2024)
This research develops children's bebe by applying the rabbit animal idea source. The type of research used is research and development with a 4D development model consisting of 4 stages, namely: definition, design, development and dissemination. The data collection method in this research was carried out by assessing children's public tests using rabbits as the animal source. The result of the development of children's bebe clothing, namely children's bebe clothing with a long torso silhouette, a low collar varied with kerinci ears whose motif is embroidered with the silhouette of a rabbit. The results of this Bebe children's clothing product have very good qualifications in public tests.